Sympatric occurrence and population dynamics of Scylla spp. in equatorial climate: Effects of rainfall, temperature and lunar phase - Hanafiah, Fazhan; Waiho, Khor; MMohammad Farhan, Darin Azri; Ismail, Al-Hafiz; Wan Ibrahim, Wan Norfaizza; Megat, Fadhlul Hazmi; Jasmani, Safiah; Ma, Hongyu; Mhd, Ikhwanuddin (Elsevier Science, Ltd., 2017)
Mud crabs (Scylla spp.) are known to exist sympatrically in the wild. However, information on their population dynamics and the influence of climate parameters and lunar phase, especially along the equatorial region, are limited. Four sampling stations representing three seas (the Strait of Malacca, South China Sea and Sulu Sea) along the equator were selected. Mud crabs were collected using baited traps during spring tides from April 2012 to July 2013. All three Scylla species, S. olivacea, S. tranquebarica and S. paramamosain live in sympatry in the three seas. Scylla olivacea is the most prevalent species in the Strait of Malacca and South China Sea, whereas S. paramamosain dominates the Sulu Sea. The total crab abundance was not affected by rainfall or temperature. The abundance of S. tranquebarica in Strait of Malacca was negatively correlated with temperature and positively correlated with rainfall whereas the abundance of S. paramamosain positively correlated with temperature only at South China Sea. Scylla tranquebarica was the largest in terms of body size and it showed interchanging abundance trends with S. paramamosain. The average body size of S. paramamosain did not differ significantly with that of S. tranquebarica and S. olivacea. This decrease is most likely attributed to overfishing. Significant seasonal fluctuations in mean carapace width were detected in S. tranquebarica and S. paramamosain, but not in S. olivacea. The monthly sex ratio of all three species occasionally fluctuates above the equal sex ratio value. Lunar phase did not affect species abundance, but males and females were significantly heavier during full moon. These findings serve as a baseline of seasonal variation in crab population dynamics that are useful in mud crab fisheries and resource management.